(untitled) (Pragyaratna प्रज्ञारत्न, 2023)
Nowadays pesticides are perceived essential for agriculture and are used extensively throughout the world. It is used for repelling, destroying or controlling pests. The objective of the study was to analyze the farmer awareness in pesticide use and its effects on health in Panchakhal Municipality. Descriptive study design and quantitative data were used. Non-probability purposive sampling method was used to select respondents. 38 farmers were selected as respondents during seven days. Interview schedule were used to collect data. The finding of the study showed that around seventy five percent male were involved to spray pesticides in commercialize vegetables. Among them, most of were young. More than fifty percent farmers were educated but they had no knowledge about proper handling of pesticides. Almost people were involved in agriculture sectors in the study area. Almost farmers used chemical pesticides in their vegetables farms to kill pests in order to increase production. Most pesticides purchasing places were agro-vet and nearby shop. Nobody took advice from agriculture office or JTA. Most of farmers had harvested vegetables just next day after spraying pesticide. Around ninety percent farmer had not taken any types of training for safe handling of pesticides as well as didn’t use personal protective equipment (PPE) properly. Farmers, who had taken basic training, almost had no health hazards. Most of them had no knowledge about proper management of empty bottles or packets of pesticides. A few percent farmers gave attention on proper personal hygiene after applying pesticides. Pesticides handling practices were not satisfactory and different health issues were reported.